The Effect of Platelet-Rich Plasma on the Zone of Stasis and Apoptosis in an Experimental Burn Model. Issue 2 (May 2019) - Uraloğlu, Muhammet; Ural, Alper; Efe, Gökhan; Yuluğ, Esin; Livaoğlu, Murat; Karaçal, Naci
Background: The zone of stasis that forms in acute burn is initially viable, but coagulation progresses to necrosis in the process that follows. Objective: This study investigates the effects of platelet-rich plasma (PRP) on apoptosis in the burn zone of stasis and on the viability of living tissue. Methods: Burns were established in the right ears of 20 female New Zealand rabbits using the "comb burn" model. Platelet-rich plasma was obtained from blood collected from rabbits' ears (n = 10) and was injected subcutaneously into the zone of stasis (n = 10). The same amount of saline solution was injected into the zone of stasis of the control group rabbits (n = 10). Histological and immunohistochemical apoptosis analysis was performed to evaluate viable areas. Results: Apoptosis levels were higher in the control group than in the experimental group. The area of viable tissue in the zone of stasis was greater than in the control group. Infection-induced neutrophil infiltration was statistically significantly lower in the experimental group. Conclusion: In this animal model, apoptosis count and viable tissue area measurement and the anti-inflammatory results in the burn area confirm that PRP therapy has a statistically significant positive impact on the survival of the zone of stasis and in acute burn injury.